An analysis of graduate theses on internet addiction in turkiye - Kurtoğlu, Elif; Pekşen Süslü, Demet (Journal of Dependence, 2024)
Objective: This study aims to examine the postgraduate theses on internet addiction in Turkey between 2007-2020 (June) in the database of the Council of Higher Education National Thesis Center. Method: The study consists of 126 theses selected via criterion sampling, which is one of the sampling types for research purposes. In the study, the descriptive content analysis method was used and document analysis was used as the data collection technique. Thesis Classification Form was used as the data collection tool. Frequency and percentage values were calculated for data analysis. Results: Tthe most studied themes were demographic-sociodemographic characteristics with personal characteristics, the number of master’s theses was more than doctoral theses, and the year in which the biggest number of studies were conducted was the year of 2019. In the examined theses, quantitative methods and simple random-random sampling techniques were mostly used. The most preferred sample size is 301-1000 people. The most preferred sample was secondary school students. Attitude/perception/personality/ability tests are the most used data collection tools. In addition, quantitative data analysis methods are used more than qualitative data analysis methods. Conclusion: There is a need to carry out more in-depth studies on internet addiction beyond descriptive studies and to establish prevention-intervention methods.